Role of baseline resting-state functional connectivity of the nucleus accumbens subregions in antidepressant treatment in major depressive disorder - Yun Wang; Jingjing Zhou; Xiongying Chen; Rui Liu; Zhifang Zhang; Yuan Feng; Yuan Zhou; Gang Wang (NeuroImage: Clinical)
The nucleus accumbens (NAc) plays a crucial role in the pathophysiology of major depressive disorder (MDD), and abnormal resting-state functional connectivity (rsFC) of NAc subregions has been found in MDD. However, it is unclear whether the altered rsFC of NAc subregions can predict the efficacy of antidepressant treatment, and whether antidepressants are capable of restoring the altered rsFC of NAc subregions in MDD. The purpose of this study was to investigate the role of rsFC of the NAc subregions in antidepressant treatment for MDD. Resting-state functional magnetic resonance imaging (fMRI) data were collected from 46 unmedicated MDD patients at baseline and after 12 weeks of escitalopram treatment, along with fMRI data from 58 healthy controls (HCs). We examined group differences in rsFC of the NAc subregions between MDD patients and HCs, explored whether the altered rsFC at baseline was associated with treatment efficacy, and evaluated whether antidepressant treatment could normalize rsFC abnormalities in the NAc subregions in MDD. Compared to HCs, MDD patients exhibited decreased rsFC between the NAc subregions and the middle cingulate cortex (MCC). Lower levels of rsFC between the NAc subregions and the MCC at baseline predicted greater improvement in depressive symptoms. Furthermore, rsFC between the NAc subregions and the MCC increased following antidepressant treatment in MDD. Our findings suggest that rsFC alterations between the NAc subregions and the MCC may serve as a potential biomarker for predicting antidepressant treatment efficacy, and that dysfunction in the frontal-ventral striatum circuitry may represent a key therapeutic target for MDD.